1988
DOI: 10.1037/0735-7028.19.3.359
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes toward the teaching of chronic pain management in doctoral clinical psychology programs.

Abstract: A questionnaire was sent to 114 graduate schools with doctoral programs in clinical psychology to gain some measure of the perceived need and importance of pain as an area of training for psychologists and to assess current educational efforts in this area. Of the 59 programs responding to the questionnaire, 13 offered a course in pain management and 46 did not offer such a course. Although 11% of all respondents agreed that a course devoted to the diagnosis of pain was needed in the curriculum, only 22% of al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2014
2014

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…Available data, although limited, tell us that most clinical psychologists are insufficiently trained in the psychosocial aspects of geriatric pain management. One survey (Siegel & Roistacher, 1988) revealed that only 22% of doctoral clinical psychology programs offered a course in pain management. More recently, in one novel dissertation study (Diamond, 2007) of 834 licensed psychologists in active practice, one in three reported having no formal education whatsoever in this area, although about 75% of the sample reported “significant exposure to pain management through informal sources” (such as discussion with colleagues).…”
Section: A Need For Further Training and Improved Service Deliverymentioning
confidence: 99%
“…Available data, although limited, tell us that most clinical psychologists are insufficiently trained in the psychosocial aspects of geriatric pain management. One survey (Siegel & Roistacher, 1988) revealed that only 22% of doctoral clinical psychology programs offered a course in pain management. More recently, in one novel dissertation study (Diamond, 2007) of 834 licensed psychologists in active practice, one in three reported having no formal education whatsoever in this area, although about 75% of the sample reported “significant exposure to pain management through informal sources” (such as discussion with colleagues).…”
Section: A Need For Further Training and Improved Service Deliverymentioning
confidence: 99%